Genetic Polymorphism of CYP2R1, CYP27A1, CYP27B1, and Vitamin D Metabolites Plasma Levels in Patients with Cardiovascular Disease: A Pilot Study - Mohamed Abouzid; Łukasz Kruszyna; Dominika Kaczmarek; Leonid Kagan; Aniceta Ada Mikulska-Sauermann; Dorota Filipowicz; Matylda Resztak; Franciszek K. Główka; Marta Karaźniewicz-Łada (Biomolecules)
The active form of vitamin D, calcitriol (1,25(OH)2D3), is produced from 25(OH)D3 via enzymes encoded by CYP2R1, CYP27A1, and CYP27B1. Polymorphisms in these genes may alter vitamin D metabolism and increase cardiovascular disease risk. This preliminary study investigated these polymorphisms in 27 patients with cardiovascular disease and 26 healthy volunteers using Polymerase Chain Reaction—Restriction Fragment Length Polymorphism (PCR-RFLP), while measuring 25(OH)D3 and 1,25(OH)2D3 concentrations by UPLC-MS/MS and ELISA, respectively. Among patients, those with the GT genotype of rs10877012 (CYP27B1) had higher 25(OH)D3 levels compared to other genotypes. Additionally, this polymorphism was associated with lower 1,25(OH)2D3 in TT homozygotes, suggesting reduced CYP27B1 activity. Furthermore, the TT genotype of rs6709815 (CYP27A1) was three times more prevalent in cardiac patients than in healthy controls, possibly indicating increased susceptibility to the disease. Although these findings suggest a genetic influence on vitamin D metabolism in cardiovascular disease, larger and more comprehensive studies are needed to confirm these associations.